Crescimento e teores de nutrientes em mudas de acerolas adubadas com ureia e superfosfato simples - Costa, Diogenes de Souza (2017)
The acerola fruit (Malpighia glabra L.) is a highly valued and sought after crop due to the high content of vitamin C in the composition of its fruits. Although it is currently a crop with economically important cultivation for several regions, there is little research related to the nutritional requirements of the acerola. Thus, the objective of this work was to evaluate the influence of nitrogen and phosphorus levels on the initial growth and mineral composition of acerola seedlings. The experiment was carried out with five doses of urea (0, 0.66, 2.25, 3.85 and 4.5 g dm-3 ) and five doses of single superfostat (SFS) (0, 0.87, 3.0, 5.13 and 6 g dm-3 ), in the randomized block design with four replicates. The experimental unit consisted of four polyethylene bags containing four seedlings in total. The stem diameter and height of the seedlings were evaluated monthly. At the end of the experiment, the length and area of the root and leaf system, the dry matter mass of the aerial part and the root system, and the N, P and K leaf contents were determined. The data were submitted to analysis of variance and regression. There was no significant interaction between urea and FSS doses. The doses of 2.13 g dm-3 urea and 2.8 g dm-3 FSS, resulted in the highest Dickson Quality Index in acerola seedlings. Leaf content of N increased with urea doses, while that of K decreased. Foliar content of P increased with single superphosphate doses.